2019
DOI: 10.1002/da.22907
|View full text |Cite
|
Sign up to set email alerts
|

Association between early‐life trauma and obsessive compulsive symptoms in community youth

Abstract: Background: Obsessive-compulsive symptoms (OCS) in youth are common, have heterogeneous manifestations, and have been shown to be associated with serious psychopathology. While early-life trauma exposure is associated with increased risk for obsessive-compulsive disorder (OCD), its association with different OCS and its clinical relevance for serious psychopathology is unclear. Here we aimed to evaluate associations among traumatic stressful events (TSE), OCS, and serious psychiatric conditions in community yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 52 publications
(77 reference statements)
2
16
0
Order By: Relevance
“…Although similar findings have been found in non-pregnant individuals (i.e., relative imbalance of HF and LF with social phobia 66 ; lower HF; and increased LF/HF ratio with PTSD 24 26 ), this is the first time pregnant women with anxiety disorders were shown to have distinct HRV patterns. Those with OCD and those with exposure to childhood traumatic events had similar alterations in ANS functioning, supported by literature showing childhood trauma exposure has been associated with greater obsessive–compulsive symptoms, particularly in females 67 . Obsessive–compulsive symptoms are more commonly seen in perinatal patients 68 , 69 .…”
Section: Discussionsupporting
confidence: 65%
“…Although similar findings have been found in non-pregnant individuals (i.e., relative imbalance of HF and LF with social phobia 66 ; lower HF; and increased LF/HF ratio with PTSD 24 26 ), this is the first time pregnant women with anxiety disorders were shown to have distinct HRV patterns. Those with OCD and those with exposure to childhood traumatic events had similar alterations in ANS functioning, supported by literature showing childhood trauma exposure has been associated with greater obsessive–compulsive symptoms, particularly in females 67 . Obsessive–compulsive symptoms are more commonly seen in perinatal patients 68 , 69 .…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, it accounts for a dimensional perspective were e.g. the exposure to a traumatic event has already been associated with an increased risk to endorsed at least one obsessive-compulsive symptom (Barzilay et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For one, there appears to be a direct association between trauma and the development of OCD symptoms (Cromer et al, 2007;Dykshoorn, 2014;Lochner et al, 2002;Real et al, 2011), with up to 70% of individuals presenting with OCD symptoms after experiencing a traumatic event (Fontenelle et al, 2012;Gershuny et al, 2008). Indeed, studies have shown that different types of trauma, such as assault, are predictive of more severe of OCD symptoms (Barzilay et al, 2019), and that past trauma is associated with greater OCD symptoms, particularly compulsions (Miller & Brock, 2017). Additionally, OCD and PTSD share some similarities in terms of symptoms, including repeated intrusive images and thoughts that produce intense anxiety and avoidance.…”
Section: Emdr and Ocdmentioning
confidence: 99%